Combination of Low-Dose Methotrexate and Cyclosporine in a Patient with Generalized Pustular Psoriasis: A Case Report - Labitta Pachira Aquaira; Nurrachmat Mulianto; Elsita Lisnawati; Hillary Fungestu Yoedyanto (Eduvest - Journal of Universal Studies, 2026)
Generalized pustular psoriasis (GPP) is a rare and life-threatening chronic inflammatory skin disease characterized by sterile pustules and systemic inflammation, associated with substantial disease burden due to frequent flares. Limited guidelines and suboptimal treatment outcomes have led to various therapeutic approaches, including combination therapy.  This case report aims to describe the use of low-dose methotrexate and cyclosporine combination in a GPP patient and evaluate the clinical response achieved.  A 40-year-old woman presented with painful pustules distributed throughout the entire body accompanied by a burning sensation. She had undergone methotrexate therapy for 1 year before self-cessation due to insignificant improvement. Dermatological examination revealed generalized multiple pustules on an erythematous base, some confluent and covered by scales. Histopathological examination showed abundant neutrophils in the superficial epidermal layer along with focal neutrophils and mild spongiosis, supporting the diagnosis of GPP. The patient was given methotrexate 7.5 mg weekly and cyclosporine 100 mg daily for 5 weeks, showing significant clinical improvement, then maintained with methotrexate 7.5 mg weekly monotherapy. Combination therapy for GPP, particularly methotrexate and cyclosporine, has demonstrated faster and better clinical responses compared to monotherapy, with response rates of 70–90%. Cyclosporine provides rapid disease control, while methotrexate offers sustained immunomodulation. Both agents carry risks of adverse effects, necessitating careful dose selection and close monitoring. This case report demonstrates that low-dose methotrexate and cyclosporine combination is effective in managing refractory GPP with significant clinical improvement after 5 weeks of therapy, making it a promising therapeutic option for severe and refractory GPP cases.